2000
DOI: 10.1007/s11940-000-0034-x
|View full text |Cite
|
Sign up to set email alerts
|

Nonepileptic seizures

Abstract: The primary goal of treatment in nonepileptic seizures (NES) is to improve the patient's quality of life by terminating seizure production or reducing seizure frequency. Initial treatment consists of explaining the diagnosis and its psychological nature to patients without judging them or giving the NES excessive attention. Next, help patients identify stresses and refer them for mental health treatment. Neurologists should continue to see patients intermittently to wean anticonvulsants, and encourage complian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This characteristic should make the diagnosis of psychogenic pseudoseizures with video‐EEG monitoring both relatively simple and readily acceptable. The certainty of a psychogenic basis for the events should then be clearly conveyed to the patient (7); this in and of itself is an initial step toward therapeutic success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This characteristic should make the diagnosis of psychogenic pseudoseizures with video‐EEG monitoring both relatively simple and readily acceptable. The certainty of a psychogenic basis for the events should then be clearly conveyed to the patient (7); this in and of itself is an initial step toward therapeutic success.…”
Section: Discussionmentioning
confidence: 99%
“…Psychogenic pseudoseizures result from various types of psychiatric disorders including dissociative disorders, affective disorders, personality disorders, and somatoform disorders (including conversion disorders) (6,7). It is reasonable, therefore, that after a diagnosis of pseudoseizures is documented in an epilepsy center, a psychiatric evaluation be requested.…”
mentioning
confidence: 99%
“…Rusch et al (32) found that matching specific psychotherapies to the patient's comorbid diagnoses produced greater seizure‐free rates, with 21 of 33 patients (63%) reaching event‐free status at the end of treatment. The pharmacologic references for NES treatment using intravenous barbiturates, tricyclic antidepressants, selective serotonin reuptake inhibitors, β‐blockers, analgesics, or benzodiazepines are anecdotal references in case reports, journal review articles, or book chapters (26,39,43, 45,46).…”
Section: Historical Aspects Of Nes Treatmentmentioning
confidence: 99%
“…Other disorders are reviewed where stress and depression clearly cause generally accepted physical disease like intestinal disorders, cardiac disease, and diabetes. An analogy of a pressure cooker has been used, where emotions are built up, their expression is blocked, and this results in an internal explosion [47]. I review the setting in which we generally find people experiencing these difficulties (ie, histories of childhood dysfunction, depression, and stress).…”
Section: Treating the Patientmentioning
confidence: 99%
“…In addition, this avoids a message of abandonment, and the patient can be monitored for the emergence of a mixed NES/ES syndrome. Bowman [47] has recommended a four-part approach involving the following:…”
Section: Treating the Patientmentioning
confidence: 99%